The impact of the two teaching strategies in the investment of learning time for the educational units of the physical education lesson (Journal of the College of Basic Education, 2022)
The research includes five chapters, where the first chapter included the introduction and the importance of the research, which confirmed and lies in the importance of the research that it will diagnose a number of problems and obstacles facing the lesson of physical education and the use of modern strategies to come up with a number of conclusions and recommendations that will contribute to addressing these obstacles and problems and work to develop the lesson of physical education. And that the research problem lies and the research problem is embodied in the low level of the physical education lesson, due to the lack of these lessons first, and the lack of interest and care for these lessons, as well as the presence of many obstacles and problems facing the physical education lesson, which need solutions in order to develop the lesson, which is the basis for raising the level of sports ,